Factors Associated with Adherence to Renal Diet among Dialysis Patients in Private Dialysis Center: A Cross-Sectional Study - Zamri, Azri Syahmi; Abdul Hamid, Syahrul Bariah; Ibrahim, Norkasihan; Dali, Ahmad Fauzi; Ramli, Siti Nur Aisyah (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2025)
This study is aimed to assess the adherence status of renal diet, determine the association between sociodemographic characteristics, dietary knowledge, nutrition literacy, and perception of recommended diet and fluid, while also identifying significant factors that play a role in influencing adherence to the renal diet within this specific healthcare setting. This cross-sectional study with purposive sampling recruited 71 of Chronic Kidney Disease (CKD) patients attending private dialysis centers in Selangor. Information on sociodemographic data, the End Stage Renal Disease Adherence Questionnaire (ESRD-AQ), the Dialysis-Related Dietary Knowledge Questionnaire (DDKQ), and the Dialysis Specific Nutrition Literacy Scale (DSNLS) were collected. The findings revealed that renal diet adherence of the respondent was 50.7%. The number of comorbidities, perception of recommended diet, and difficulty in watching diet recommendations were associated with adherence to renal diet among the participants. Further analysis using multivariate logistic regression revealed that the number of comorbidities (AOR=9.22, 95% CI:2.10˗40.47) and the difficulty in watching diet recommendations (AOR=0.04, 95% CI:0.003˗0.13) were significant determinants of dietary adherence. Dialysis patients with a higher number of comorbidities have a stronger likelihood of dietary adherence, meanwhile those with difficulty in watching diet recommendations have a higher tendency to non-adherence to renal diet. Thus, the difficulty identified should be overcome to improve renal diet adherence in the future.